Hubungan Ketersediaan Air Bersih dan Jamban Sehat dengan Kejadian Diare di Desa Bumban Kecamatan Nibong Kabupaten Aceh Utara - Nada Nur Kamaria; Hafni Zahara; Erna Safitri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Diarrhea is the second leading cause of death among children under five, responsible for approximately 525, 000 deaths in 2023, as reported by WHO. This study used a quantitative approach with a case-control design to analyze the relationship between clean water access, latrine ownership, and diarrhea incidence in Bumban Village, North Aceh Regency. The population consisted of 54 family cards, with limited access to clean water and healthy latrines. Data were analyzed using univariate and bivariate approaches, with the Chi-Square test determining relationships. The results revealed that 61.2% of clean water sources met health standards, while 38.8% did not. Additionally, 75.9% of respondents had latrines, while 24.1% did not. A p-value of 0.059 indicated a relationship between clean water availability and diarrhea incidence, while a p-value of 0.000 showed a significant relationship between latrine ownership and diarrhea. Among respondents with clean water meeting health standards, 36.4% experienced diarrhea, compared to 63.6% with non-compliant water. Similarly, 27.3% of those with latrines experienced diarrhea, while 72.7% without latrines did. These findings emphasize the significant role of clean water and latrines in preventing diarrhea.